Dynamic Interactions between FDI and Economic Growth in China: An ARDL Analysis - Jiaying, Li; Ridzuan, Abdul Rahim; Almaamari, Qais Ahmed; Al Absy, Mujeeb Saif Mohsen; Mukthar, K.P. Jaheer; Abd Samad, Khairunnisa; Abd Rahman, Nur Hayati (International Journal of Economics and Financial Issues, 2025)
The Chinese economy has benefited from foreign direct investment (FDI) by facilitating capital accumulation, technological transfer, industrial upgrading, and employment creation. However, the complexity of the relationship between FDI and economic growth persists, contributed by factors like global economic shifts, policy adjustments, and structural transformations. Thus, this study looked at the impact of FDI on influencing economic growth in China in terms of the short-term and long-term impacts. This study utilized the Autoregressive Distributed Lag or the ARDL model, covering data spanning from 1990 to 2023. This study responds to the need to fill the literature gap, including the absence of long-term dynamic analysis, limited empirical studies incorporating post-2020 data, and the neglect of asymmetric effects in the FDI-growth relationship. Empirical findings indicate that while FDI has historically driven economic expansion, its effectiveness varies across different economic stages, with potential crowding-out effects or dependency issues emerging over time. Moreover, recent geopolitical tensions, trade disruptions, and structural shifts in FDI composition have significantly altered its impact on GDP growth. The study concludes that optimizing FDI quality, fostering domestic enterprise competitiveness, and enhancing governance frameworks are essential for maximizing the positive effects of FDI in China, allowing China to grow its economy sustainably. The findings provide valuable insights for policymakers in designing effective foreign investment strategies that align with China’s evolving economic landscape.